The correlation between intestinal metaplasia typesand PCNA/Ki 67 proliferative index - Elif GÜRER İNANÇ; Güzide GÖKHAN; Tekinalp GELEN; Figen SARGIN; Mehmet A. ÖZGÜR (Turkish Journal of Gastroenterology, 2019)
-